Economic Effect of Regulatory Reforms in Korea - Jungwook Kim (Korea Development Institute (KDI), 2016)
This paper adapts the World Bank Regulatory Quality Index (RQI) which is produced annually to have better understandings on effects of regulatory reforms, instead of the Production Market Regulation (PMR) indicators published every 5 years. Firstly, this analysis indicates that GDP per capita will be raised by 17~29.8% when the index increases by one unit. Secondly, we find that 9.9 to 32.2 billion USD worth of regulatory cost could be reduced, if the regulatory quality in Korea improves to the level of the OECD average considering that the total burden of regulation in Korea is estimated 2.2 to 354.7 billion USD. The estimate of regulatory cost reduction takes roughly 0.76 to 2.47% of Korea's GDP in 2013, underscoring the importance of regulatory reforms for the Korean economy.
Keywords: 330